Probabilistic Energy Flow Analysis for Integrated Energy Systems Considering Correlated Uncertainties. Issue 1 (January 2021) - Yuan, Xu; Haifeng, Cen; Tao, Li; Wu, C.Q.; Zheng, J. H.
Abstract: The integrated energy systems (IES) contain various energy sub-systems, thus uncertainties of one sub-system will not only threaten its own safety operation but also be likely to have a significant impact on the operation of other sub-systems. Therefore, it is of great significance to study the variation of state variables when random fluctuations emerge in the IES. This paper proposes a unified steady state probabilistic energy flow (PEF) analysis for the IES considering the correlated uncertainties. Firstly, a Latin hypercube sampling with inverse Nataf transformation is developed to deal with correlated uncertainties of the IES. Furthermore, in order to solve the PEF problem, a unified method, Newton-Raphson embedded with Newton Downhill technique, is proposed to accelerate the iteration and improve the computation efficiency. The effectiveness of the proposed PEF analysis method is verified by a set of test results conducted on an IES composed of the IEEE 118-bus system coupled with 15-natural gas system and 32-district heating system.